Kepastian Hukum Akta Pembagian Hak Bersama Karena Perceraian Terkait Sertifikat Hak Atas Tanah yang di Blokir - Syatria Novyardi Rialdo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The aim of this research is to examine the legal certainty of deeds of sharing joint rights due to divorce related to blocked land title certificates. The type of research that will be used is normative. The research approach is carried out using the statutory approach, case approach, conceptual approach and analytical approach. Sources of legal materials used in normative legal research consist of primary, secondary and tertiary legal materials. Data analysis techniques by collecting legal materials and other sources of legal materials that are relevant to the legal issues being studied. Analysis of legal materials carried out in this research is legal interpretation (interpretation) and legal construction methods, namely grammatical interpretation, systematic interpretation. Legal certainty regarding the Deed of Sharing of Joint Rights regarding divorce is based on the Civil Code, the Marriage Law and legal regulations regarding land so that the process of transferring land rights can be carried out.